Do natural resources depress income per capita? - Van der Ploeg, R; Arezki, R (University of Oxford, 2008)
Most evidence for the resource curse comes from cross-country growth regressions suffers from a bias originating from the high and ever-evolving volatility in commodity prices. This paper addresses these issues by providing new cross-country empirical evidence for the effect of resources in income per capita. Natural resource dependence (resource exports) has a significant negative effect on income per capita, especially in countries with bad rule of law or bad policies, but these results weaken substantially once we allow for endogeneity. However, the more exogenous measure of resource abundance (stock of natural capital) has a significant negative effect on income per capita even after controlling for geography, rule of law and de facto or de jure trade openness. Furthermore, this effect is more severe for countries that have little de jure trade openness. These results are robust to using alternative measures of institutional quality (expropriation and corruption instead of rule of law).